2023
DOI: 10.1001/jamanetworkopen.2022.56152
|View full text |Cite
|
Sign up to set email alerts
|

Association of Post–COVID-19 Condition Symptoms and Employment Status

Abstract: ImportanceLittle is known about the functional correlates of post–COVID-19 condition (PCC), also known as long COVID, particularly the relevance of neurocognitive symptoms.ObjectiveTo characterize prevalence of unemployment among individuals who did, or did not, develop PCC after acute infection.Design, Setting, and ParticipantsThis survey study used data from 8 waves of a 50-state US nonprobability internet population-based survey of respondents aged 18 to 69 years conducted between February 2021 and July 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…Evidence on the impact of PCC on the occupational situation and work-related impairments due to PCC is limited and heterogenous (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Prior studies have reported that between 11% and 50% of individuals do not return to work (2,14,26) and that 10% to 72% do not fully regain their work capacity 6 to 12 months after infection (7,23,26,27).…”
Section: Main Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on the impact of PCC on the occupational situation and work-related impairments due to PCC is limited and heterogenous (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Prior studies have reported that between 11% and 50% of individuals do not return to work (2,14,26) and that 10% to 72% do not fully regain their work capacity 6 to 12 months after infection (7,23,26,27).…”
Section: Main Findings In Contextmentioning
confidence: 99%
“…Few studies have evaluated the association of PCC with work-related functioning or subsequent occupational changes (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Most focused on describing work absenteeism and found that 11%-50% of workers do not return to work several months after COVID-19 (2,14).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Collectively, known as Post-Covid-19 condition or long Covid and shown to have significant impact on quality of life. [5][6][7][8][9] While our knowledge of the long-term health consequences of Covid-19 continues to advance, the full range of implications is not yet fully understood. In addition, SARS-CoV-2 infection may have a prolonged effect on both the innate and adaptive immune system.…”
Section: Introductionmentioning
confidence: 99%
“…PCS can lead to a health-related decline in quality of life and interferes with daily life and activity [7,8]. Patients may develop comorbidities such as anxiety disorders, depression and cognitive symptoms, reducing the likelihood of employment and working full time [9,10], highlighting the socioeconomic impact of PCS.…”
Section: Introductionmentioning
confidence: 99%